HISTOLOGY OF IMMUNE SYSTEM ORGANS - Azizbek Komiljonov; Fozilkhon Shukurullokhonov; Jamshid Kamilov; Gulasal Ernayeva (Modern American Journals, 2025)
The immune system consists of complex structures that protect the body from external and internal pathogenic factors. This article provides a comprehensive analysis of the histological structure of immune system organs, their functional characteristics, and their role in the formation of immunity. Special attention is given to the microscopic structure of central immune organs (thymus and bone marrow) and peripheral immune organs (spleen, lymph nodes, Peyer's patches, and tonsils).